Information Technology (IT) in college formation: Achievements and challenges in Psychology and Education - Rivero, Carol (2016)
The present study aims to develop significant learning in college students through active and participative learning methods that promote autonomy and self-reflection. Study 1 aims to explore students´ perceptions of the use of clickers in Psychology students. Participants were 60 college students ages 19 to 26 (M = 21.12, SD = 1.47) who answered a 40-item multiple alternative likert-scale with additional open-ended questions. Results revealed perceived benefits (class dynamic, theory review and reinforcement), and perceived uses (debates, experiments, evaluations with immediate reinforcement, and knowledge verification). It is concluded that the use of clickers in undergraduate formation in Psychology is an effective tool to introduce IT to support students´ learning process. Study 2 is an exploratory study using flipped classroom with 5th semester preschool and primary education students, using active methods inside, and outside the classroom. Results revealed that college students tend to internalize better the theoretical concepts, and display better levels of motivation, as well as satisfaction with their achievements.